Advanced concepts for intelligent vision systems : 20th International Conference, ACIVS 2020, Auckland, New Zealand, February 10-14, 2020, Proceedings /: 20th International Conference, ACIVS 2020, Auckland, New Zealand, February 10-14, 2020, Proceedings. (2020) - Unknown
No abstract available